Analysis of Pro-Poor Policies in the Governance of Aceh’s Special Autonomy Funds - Renaldi Safriansyah, Renaldi Safriansyah; Muhammad Asri Bin Mohd Ali, Muhammad Asri Bin Mohd Ali (JOURNAL OF GOVERNMENT SCIENCE, 2025)
The acceleration of poverty reduction is one of the priority areas in the governance of Aceh’s special autonomy funds. However, after almost twenty years of policy implementation, the poverty level remains relatively high, and the efforts to effectively target poverty still pose a major challenge. Existing studies showed a lack of analysis on the pro-poor aspect of the policy, which can be reflected in public expenditure. This study analyzes the composition of Aceh’s public spending in priority areas and assesses the extent of policy pro-poorness in the implementation of special autonomy funds. A panel of experts established a weighting system for each policy, and subsequently, an overall ranking was derived by merging the individual rankings. This was accomplished by aggregating all rankings and computing the average through the process of adding them together and dividing by the total count of rankings. Qualitatively, the rating for assessment of policy pro-poorness in the implementation of Aceh's special autonomy funds is classified on a scale of high, medium, and low. The results show that spending on special autonomy funds is highly prioritized towards areas with a long-term impact on poverty reduction, while policies with short-term impacts on poverty reduction are still limited. In light of our findings, it is recommended that the Aceh government increase the spending of the special autonomy fund on economic empowerment and poverty reduction, prioritizing the remaining funds for their immediate impact on poverty reduction.